Alternative nutritional supplement for animal feed based on Chinese Potato (Colocasia esculenta) and banana (Musa x paradisiaca) (Journal of Pharmaceutical Negative Results, 2022)
The processing was done to obtain flour from Chinese potato (Colocasia esculenta) and rejection banana (Musa x paradisiaca). The objectives were to determine the best level of antioxidants for the mixture, determine the best drying parameter of times and temperatures, and carry out the economic analysis of the treatments under study. A multifactorial statistical design (2 *2*3) was used, with 12 treatments and two replicates totaling 24 experimental units. To establish the nutritional components of the banana and Chinese potato rejection flours and combination, through bromatological analysis, in addition to establish adequate ranges for drying, for conservation with the highest amount of nutrients. The factors under study: first-factor raw materials; counted with two Chinese potatoes and banana rejection; (Pch and Reb); the second factor with two ranges 0C Celsius (T0 at 60°C 4 hours and 65°C and 5 hours) and, third factor three percentages of antioxidants (Aci, Aas, Bs) citric acid, ascorbic acid and sodium metabisulfite, being its results the following, protein for the Chinese potato flour with 6.79; at a temperature of 5,870 C of the temperature range T65° and 5 hours; with the addition of the antioxidant ascorbic acid of 6.16%; representing an economically viable alternative. While for optimal antioxidants and conservation of nutritional elements, ascorbic acid at 0.05% contains more protein and crude fiber. About granulometry, the two raw materials meet the conditions established by NORMA INEN 2051:95 (1995), thus determining their use in flours for animal consumption.